Dietary inflammatory index and breast cancer risk: an updated meta-analysis of observational studies - Hayati, Zahra; Jafarabadi, Mohammad Asghari; Pirouzpanah, Saeed (European journal of clinical nutrition, 2022)
This updated meta-analysis sought to determine whether the pro-inflammatory potential of diet is a risk factor for breast cancer (BrCa) development, for the first time focusing on the effects of design heterogeneity. The search was performed using Scopus, PubMed, and Embase databases. Data were extracted from twenty-one eligible studies, including eleven cohorts (336,085 participants/20,033 incidence cases), and ten case-control studies (9,833 cases/12,752controls). The random-effect was used to calculate the relative risk (RR) using STATA 16 software. The highest dietary inflammatory index (DII) vs. the lowest category showed 16% increased risk of BrCa (95% CI: 1.06–1.26; I 2 = 62.8%, P ( I 2 ) < 0.001). This was notable in post-menopausal status (RR = 1.13, 95% CI: 1.04–1.22), women with body mass index (BMI) ≥ 30 kg/m 2 (RR = 1.35, 95% CI: 1.07–1.63), and study populations from developing countries (RR = 1.79, 95% CI: 1.12–2.47). Methodological covariates were subject to subgroup meta-analyses and showed stronger results among case-control studies (RR = 1.50, 95% CI: 1.20–1.80), studies considered age-matched controls (RR = 1.56, 95% CI: 1.19–1.93) and hospital-based controls (RR = 2.11, 95% CI: 1.58–2.64), and cohort studies identified by prolong follow-up durations (RR = 1.13, 95% CI: 1.03–1.22). This updated meta-analysis highlighted the pro-inflammatory diet as a risk factor for BrCa, especially among women in post-menopausal status, obese groups, and developing countries. Meta-analysis in methodological subgroups could improve results, less affected by heterogeneity, and suggested subclassification with important implications for future epidemiological designs and even clinical management.